Perceived discrimination and refraining from seeking physician's care in Sweden: an intersectional analysis of individual heterogeneity and discriminatory accuracy (AIHDA) - Mariam Hassan; Johan Öberg; Maria Wemrell; Raquel Perez Vicente; Martin Lindström; Juan Merlo (BMC, 2024)
Abstract Background Discrimination may further impede access to medical care for individuals in socially disadvantaged positions. Sociodemographic information and perceived discrimination intersect and define multiple contexts or strata that condition the risk of refraining from seeking physician's care. By applying analysis of individual heterogeneity and discriminatory accuracy (AIHDA) we aimed to improve the mapping of risk by considering both strata average risk differences and the accuracy of such strata risks for distinguishing between individuals who did or did not refrain from seeking physician's care. Methods We analysed nine annual National Public Health Surveys (2004, 2007-2014) in Sweden including 73,815 participants. We investigated the risk of refraining from seeking physician's care across 64 intersectional strata defined by sex, education, age, country of birth, and perceived discrimination. We calculated strata-specific prevalences and prevalence ratios (PR) with 95% confidence intervals (CI), and the area under the receiver operating characteristic curve (AUC) to evaluate the discriminatory accuracy (DA). Results Discriminated foreign-born women aged 35-49 with a low educational level show a six times higher risk (PR = 6.07, 95% CI 5.05-7.30) than non-discriminated native men with a high educational level aged 35-49. However, the DA of the intersectional strata was small (AUC = 0.64). Overall, discrimination increased the absolute risk of refraining from seeking physician's care, over and above age, sex, and educational level. Conclusions AIHDA disclosed complex intersectional inequalities in the average risk of refraining from seeking physician's care. This risk was rather high in some strata, which is relevant from an individual perspective. However, from a population perspective, the low DA of the intersectional strata suggests that potential interventions to reduce such inequalities should be universal but tailored to the specific contextual characteristics of the strata. Discrimination impairs access to healthcare.